The Effectiveness of Mozart Classical Music Therapy in Reducing Anxiety Levels in Third-Term Pregnant Women at the Bunda Fatimah Midwife Clinic in 2025 - Roslina Julianti; Suyanti Suwardi; Dian Zuiatna (Journal of Innovative and Creativity, 2025)
Anxiety in the third trimester of pregnant women can result in postpartum parenting stress and will affect the labor process which will result in weak uterine contractions, prolonged labor, fetal distress, increased maternal blood pressure which causes mortality and morbidity, at the Bunda Fatimah Clinic there are 13 pregnant women in the third trimester who experience anxiety, of these 13 pregnant women said that they were worried about the condition and state of the fetus in their womb, afraid of bleeding, afraid of facing labor, worried about their irregular emotional state, as a result of the anxiety that occurs in pregnant women in the third trimester. The study purpose was This study aims to determine the effectiveness of Mozart's classical music therapy in reducing anxiety in pregnant women in the third trimester at the Bunda Fatimah Clinic in 2025. Materials and methods. This study used a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 13 pregnant women in their third trimester selected using accidental sampling. The intervention consisted of listening to Mozart classical music once every three days for 15 minutes. Data analysis used a paired sample t-test. Results. Research Results Before the intervention, respondents experienced no anxiety (7.7%), mild anxiety (7.7%), moderate (61.5%), severe (23.1%), and very severe (0%). After the intervention, the anxiety level changed to no anxiety (31%), mild (61%), moderate (8%), and severe (0%). The results of the statistical test showed a P-Value = 0.001 < 0.05, meaning that H₀ was rejected and Hₐ was accepted, so that Mozart classical music therapy was proven to be effective in reducing anxiety. Conclusions. The conclusion of this study is that Mozart classical music therapy can reduce anxiety in pregnant women during the third trimester. The researchers recommend that respondents apply this therapy to reduce anxiety levels in pregnant women during the third trimester and increase comfort during pregnancy.